2002
DOI: 10.1128/iai.70.9.5279-5282.2002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Domain of Bovine Milk Lactoferrin Which Inhibits the Adherence of Streptococcus mutans Cells to a Salivary Film

Abstract: The bovine lactoferrin molecule and relatively long lactoferrin fragments containing residues 473 to 538 strongly inhibited adherence of Streptococcus mutans to saliva-coated hydroxyapatite beads. Each cysteine residue in Lf411 (residues 473 to 538) was replaced by a serine residue, and the mutants Lf411-C481S and Lf411-C532S strongly inhibited S. mutans adherence. These results suggest that the functional domain of lactoferrin that binds to a salivary film lies in residues 473 to 538 and that the region might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 19 publications
1
29
1
Order By: Relevance
“…Both WPI and SWPC80 showed similar trends whether saliva was present or not, and lactoferrin was observed to be effective at inhibiting adherence of S. mutans to both PBS-HA and S-HA. This component of milk has previously been shown to be a potent inhibitor of adhesion of S. mutans (strain MT8148) to S-HA beads, and the findings of the present study are consistent with the work of Oho and co-workers [25]. It is well known that consumption of milk can be protective against occurrence of dental caries, and a study by Vacca-Smith et al [26] reported that treatment of S-HA beads with milk caused a reduction in the adherence of S. mutans GS-5.…”
Section: Assessment Of Anti-adhesive Effect Of Milk Componentssupporting
confidence: 83%
“…Both WPI and SWPC80 showed similar trends whether saliva was present or not, and lactoferrin was observed to be effective at inhibiting adherence of S. mutans to both PBS-HA and S-HA. This component of milk has previously been shown to be a potent inhibitor of adhesion of S. mutans (strain MT8148) to S-HA beads, and the findings of the present study are consistent with the work of Oho and co-workers [25]. It is well known that consumption of milk can be protective against occurrence of dental caries, and a study by Vacca-Smith et al [26] reported that treatment of S-HA beads with milk caused a reduction in the adherence of S. mutans GS-5.…”
Section: Assessment Of Anti-adhesive Effect Of Milk Componentssupporting
confidence: 83%
“…The overall clinical function of lysozyme and lactoferrin in the human mouth is not well documented, suggesting instead that they are important for controlling the microbial overgrowth, reducing the number of bacteria in the dental biofilm, decreasing the colonization of microorganisms and/ or modifying the bacterial metabolism (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…[53] -apo-hLf caused cell lysis -The mechanism involved was caused by the binding of proteins to amoeba membrane E. histolytica HM 1:IMSS bLf, apo-hLf and bLfcin (6) (fragment [4][5][6][7][8][9][10][11][12][13][14] [ ]* 1.0, 2.5 -bLf and hLf were amoebicidal [54] -Effect was concentration-dependent and modulated by environmental conditions -bLf was more effective than bLfcin -All components synergized with metronidazole vs amoebae E. histolytica HM 1:IMSS bLfcin, bLfampin and bLf chimera (7) [ ]* 0.025, 0.050, 0.075, 0.10 -bLfcin and bLfampin had a moderate amoebicidal effect [55] -bLfcin chimera showed the highest microbicidal activity -The microbicidal effect of Lf peptides was iron-independent G. duodenalis bLf, bLfcin, hLf, Lfcin (2) [ ]* bLfcin and hLfcin: 0-0.024; bLf and hLf: 0-2.5 -LD50: bLfcin: 8 (µg/ml); bLf: 1.2 (mg/ml); hLfcin: 16 (µg/ml); hLf: 1.5 (mg/ml)…”
Section: In Vitro Assaysmentioning
confidence: 99%
“…In addition, Lf is bactericidal, by binding to lipopolysaccharide (LPS), porins, and other outer membrane (OM) proteins in Gram-negative bacteria [6]; likewise, Lf can bind to teichoic acid in Gram-positive bacteria. All these actions cause disruption of the bacterial membrane, leading to cell lysis [7,8] bLf affects biofilm production [9][10][11], diminishes the release of toxins [12], and interferes with the adhesion of bacteria to host cells [9,[13][14][15][16]. Moreover, Lf synergizes with antibiotics, potentiating their antimicrobial effect [17][18][19].…”
Section: Introductionmentioning
confidence: 99%